Immunological characterization and function analysis of L-type lectin from spotted knifejaw, Oplegnathus punctatus - Liu, Jinxiang; Liu, Xiaobing; Wang, Zhigang; Zhang, Quanqi (Frontiers in Immunology, 2022)
Lily-type lectin (LTL) plays significant roles in innate immune response against pathogen infection. LTL in animals and plants has received widespread attention. In the present study, an LTL (OppLTL) was identified from spotted knifejaw Oplegnathus punctatus. The OppLTL encoded a typical Ca2+-dependent carbohydrate-binding protein, containing a CRD domain. qRT-PCR showed that it was mainly expressed in the gill, and was significantly up-regulated after Vibrio anguillarum challenge. Agglutination analysis showed that the recombinant OppLTL could bind and agglutinate Gram-negative and Gram-positive bacteria in a Ca2+-dependent manner. However, the binding activity was different. Meanwhile, The recombinant OppLTL could hemagglutinate mammalian and teleost erythrocytes. Subcellular localization revealed that OppLTL was mainly detected in the cytoplasm of HEK293T cells. Dual-luciferase analysis revealed that OppLTL could inhibit the activity of the NF-κB signal pathway in HEK293T cells after OppLTL overexpression. These findings collectively demonstrated that OppLTL could be involved in host innate immune response and defense against bacterial infection in spotted knifejaw.